Migratory neurons in adult songbirds spread their wings - Shawn F. Sorrells (Cell Reports, 2024)
Throughout the life of the adult songbird, neurons are recruited into brain regions important for song learning. Movies captured by Shvedov et al. demonstrate this dynamic process in the live animal, revealing the mechanisms of neuronal migration in the adult brain.